Utilization of Cigarette Putt Waste as Reinforcement in Normal Fiber Composite Materials to Increase Tensile Strength - Anggun Dwi Setia NIngsih; Wanda Cahyaning Ati; Fauzi Agil Amirza; Rido Fabian Naufal; Denny Oktavina Radianto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the mechanical properties of fiberglass composites made from normal fiberglass and a mixture of cigarette waste. The research was conducted using three treatments, namely normal fiberglass, mixed fiberglass 1, and mixed fiberglass 2. The method used was experimental with one replication. The results showed that fiberglass mixed with cigarette waste has a lower maximum force value compared to normal fiberglass. Therefore, mixed fiber specimens with cigarette filter fiber mixed materials can be used as an alternative material to replace normal fibers.